The Use of a “Tt” Shaped Cannula for Collection of Duodenal Digesta in Sheep - Borhami, B. E. A. (Acta Vet Scand, 1980)
Six sheep were equipped with both a rumen fistula and a duodenal cannula. The duodenal cannula was made of two ordinary T shape cannulas which were vulcanized into a double T cannula. Both the rumen and the duodenal cannulas were made of soft rubber. In two experiments six different diets were fed. In the first experiment the diets consisted mainly of ammonia-treated straw (NH3-straw) plus barley or sodium hydroxide-treated straw (NaOH-straw) plus concentrate containing different N-supplements. In the second experiment, the treated straw (either NH3-straw or NaOH-straw) was fed alone. The animals in the two experiments were fed at maintenance level. Duodenal digesta were collected for periods of 12 h by inflating a balloon in the distal flange of the cannula, using pieces of foam rubber. The volume of fluid leaving the rumen was measured using the marker Gr-EDTA. The effect of digesta removal on blood constituents was studied. Three to four observations on each ration were made. Digesta flow and dry matter entering the duodenum were higher with NH3-straw than NaOH-straw fed either alone or with concentrate. However, there was a considerable variation of which a large part was of individual nature. The volume of fluid reaching the duodenum was always lower than the volume leaving the rumen, indicating a net absorption of water in the omasum and abomasum. This was estimated to be from 10.1 to 11.6 1/24 h in Experiment 1 and from 0.3 to 1.4 1/24 h in Experiment 2 (51–59 and 5–31 % of the ruminai outflow, respectively). A significant increase in plasma K and Mg and decrease in P(i) and a-amino N concentration were observed due to 12 h collection of duodenal digesta. However, plasma Na, Ca, glucose and urea nitrogen concentrations remained at their pre-collection levels. Post-mortem examination of duodenum in sheep slaughtered after six and 10 months revealed a normal gut with no sign of dilatation in the immediate vicinity of the cannula.